Fungal Endophytes Exert Positive Effects on Colobanthus quitensis Under Water Stress but Neutral Under a Projected Climate Change Scenario in Antarctica - Hereme, Rasme; Morales-Navarro, Samuel; Ballesteros, Gabriel; Barrera, Andrea; Ramos, Patricio; Gundel, Pedro E.; Molina-Montenegro, Marco A. (Frontiers in Microbiology, 2020)
Functional symbiosis is considered one of the successful mechanisms by which plants that inhabit extreme environments improve their ability to tolerate different types of stress. One of the most conspicuous types of symbiosis is endophyticism. This interaction has been noted in Colobanthus quitensis, a vascular plant capable of inhabiting such stressful environments as the Antarctic, which stands out for being one of the most severe environments on earth and is characterized by its low temperatures and extreme aridity. However, it has been suggested that one of the adaptation mechanisms of C. quitensis is its association with endophytic fungi. Projections of climate change for this ecosystem indicate that abiotic conditions will be less limiting due to an increase in temperature and the availability of water in the soil. Due to this decrease in stress induced by climate change, it has been suggested that the positive role of endophytes may decrease. This study evaluates the role of endophytic fungi on osmoprotective molecules (sugar production, proline, oxidative stress) and gene expression (CqNCED1, CqABCG25 and CqRD22) as well as functional traits (stomatal opening, net photosynthesis and stomatal conductance) in individuals of C. quitensis. Individual plants of C. quitensis with (E+) and without (E-) endophytic fungi were exposed to simulated conditions of increased water availability (W+), having the current limiting water condition (W-) in Antarctica as control. The results reveal an endophyte-mediated lower oxidative stress, higher production of sugars and proline in plants. In addition, E+ plants showed differential expressions in genes related with drought stress response, which was more evident in W- than in W+. These parameters corresponded with increased physiological mechanisms such as higher net photosynthesis, stomatal opening and stomatal conductance under presence of endophytes (E+) as well as the projected water condition (W+). These results suggest that the presence of endophytes play a positive role, favoring tolerance to water stress in C. quitensis. However, this positive role would be diminished with an increase in water availability (W+), suggesting that biotic interactions could decrease in importance as a strategy for tolerating prevailing environmental conditions in Antarctica under a future scenario of climate change.